Arts Journalism In The Digital Era: Challenges, Transformations, And Innovative Strategies: CHALLENGES, TRANSFORMATIONS, AND INNOVATIVE STRATEGIES - Pribadi, Firman; Wastap, Jaeni B (ARRUS Journal of Social Sciences and Humanities, 2025)
Arts and culture journalism in Indonesia faces major challenges in the era of digital transformation, which is characterized by the lack of regeneration of journalists, the dominance of digital algorithms, and economic pressures that shift the focus of news from the substance of art to entertainment. This research aims to analyze the main challenges in the regeneration of arts and culture journalists, understand the impact of media transformation on art reporting, and offer strategic solutions for the revitalization of arts and culture journalism. Using a case study-based descriptive qualitative method, data was collected through in-depth interviews with senior cultural arts journalists and founders of digital art news platforms, as well as document analysis and literature reviews. The results show that the main challenges include a lack of economic incentives, the dominance of social media algorithms that prioritize popularity over depth of analysis, and low institutional support for the cultural arts rubric. However, revitalization opportunities can be realized through digital technology-based approaches, creative strategies such as the integration of pop culture and lifestyle, and collaborations between the media, art communities, and educational institutions. This study emphasizes the importance of applying encoding/decoding (Hall) and gatekeeping (McQuail) theories in understanding the paradigm shift in cultural arts journalism in the digital era, as well as offering a strategic framework to create a relevant, inclusive, and sustainable art journalism ecosystem.